2012
DOI: 10.1242/dev.089946
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of multiple target genes by miR-1 and miR-206 is pivotal for C2C12 myoblast differentiation

Abstract: SummaryMicroRNAs are short non-coding RNAs involved in post-transcriptional regulation of multiple messenger RNA targets. The miR-1/ miR-206 family is expressed during skeletal muscle differentiation and is an integral component of myogenesis. To better understand miR-1/miR-206 function during myoblast differentiation we identified novel target mRNAs by microarray and characterized their function in C2C12 myoblasts. Candidate targets from the screen were experimentally validated together with target genes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 24 publications
1
28
0
2
Order By: Relevance
“…Interestingly, this regulation was limited to the JR1 eRMS cell line, as similar repression of Pax3 was not observed in the more commonly studied Rh30 aRMS cells . Other miR‐206 targets that interfere with myogenic differentiation by regulating myoblast proliferation and survival were also recently described . Previous studies have shown that Pax3 is expressed in myogenic precursors, and analogously to Pax7, functions as an inhibitor of terminal differentiation .…”
Section: Downstream Effects Of Myod Dysregulation In Rmsmentioning
confidence: 66%
“…Interestingly, this regulation was limited to the JR1 eRMS cell line, as similar repression of Pax3 was not observed in the more commonly studied Rh30 aRMS cells . Other miR‐206 targets that interfere with myogenic differentiation by regulating myoblast proliferation and survival were also recently described . Previous studies have shown that Pax3 is expressed in myogenic precursors, and analogously to Pax7, functions as an inhibitor of terminal differentiation .…”
Section: Downstream Effects Of Myod Dysregulation In Rmsmentioning
confidence: 66%
“…Myogenic miRNAs are critical regulators of SC differentiation and growth, have important roles in muscle remodeling, and their dysregulation has been implicated in diseases of cardiac and skeletal muscle. Numerous downstream miR‐1/miR‐206 targets have been identified in C2C12 cells, but the specific role of miR‐1/miR‐206 family members in myoblast differentiation remains to be determined (52).…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 myoblasts were maintained in DMEM (Sigma‐Aldrich) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (Sigma‐Aldrich; Goljanek‐Whysall et al, 2012). For cholesterol‐linked miR‐181a mimic, antagomiR‐181a, or antagomiR scrambled, 50% confluent C2C2 myoblasts were treated at 100 nM final concentration for 48 hr previous to treatment with 10 µM CCCP or 100 nM bafilomycin A (both Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%